2012
DOI: 10.1007/s13312-013-0067-3
|View full text |Cite
|
Sign up to set email alerts
|

Expressed breast milk vs 25% Dextrose in procedural pain in neonates: A double blind randomized controlled trial

Abstract: EBM significantly reduces procedural pain in neonates though to a lesser extent as compared to 25% dextrose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 18 publications
3
21
0
1
Order By: Relevance
“…Neonates in 25% dextrose group had statistically significant lower PIPP score and reduced cry time after venepuncture. Similarly, studies conducted by Sahoo et al (6) and Mariano et al (11) also showed that 25% dextrose decreased mean PIPP score and cry time after procedure compared to placebo . Costa et al aimed to evaluate the effect of 25% glucose during ophthalmic examination for retinopathy of prematurity in preterm infants using Neonate infant pain scale.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Neonates in 25% dextrose group had statistically significant lower PIPP score and reduced cry time after venepuncture. Similarly, studies conducted by Sahoo et al (6) and Mariano et al (11) also showed that 25% dextrose decreased mean PIPP score and cry time after procedure compared to placebo . Costa et al aimed to evaluate the effect of 25% glucose during ophthalmic examination for retinopathy of prematurity in preterm infants using Neonate infant pain scale.…”
Section: Discussionmentioning
confidence: 71%
“…(4) In addition to short term effects, evidence have demonstrated that neonatal pain influences (5) Neonates lack the ability to verbalise pain and hence caregivers must be able to recognise, assess and manage pain. (6) Various types of pharmacologic and non pharmacologic methods have been described for neonatal pain management. (7) Recent Cochrane reviews have discussed non pharmacologic interventions to reduce pain in neonates during routine procedures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Many such studies have proved that oral dextrose (different concentrations have been used in different studies) reduced the crying time of infants experiencing procedural pain. [8][9][10][11] The other methods commonly used for management of pain include expressed breast milk, non-nutritive sucking or oral sucrose.…”
Section: Discussionmentioning
confidence: 99%
“…Estudos acerca da dor neonatal têm avaliado características específicas do choro relacionado à estimulação dolorosa no RN (GRUNAU; CRAIG; JOHNSTON, 1990;STRADA, 1986), bem como diferenças em sua frequência fundamental em distintas idades gestacionais (GIBBINS et al, 2008;JOHNSTON et al, 1993), duração do choro (BUCHER et al, 2000;BUENO et al, 2012;CASTRAL et al, 2012;BLASS;MILLER, 2001;OZDOGAN et al, 2010;SAHOO et al, 2012) Cabe destacar que o exame de fundo de olho é um procedimento que provoca dor severa (CIGNACCO et al, 2008), manifestada por aumento da FC e pressão arterial, queda da saturação de oxigênio, mímica facial de dor e choro, especialmente durante a inserção do espéculo (DHALIWA et al, 2010;KANDASAMY et al, 2011;KIRCHNER et al, 2009 Uma explicação para essa resposta pode estar relacionada ao fato de os RNPTs estarem exaustos após o exame de fundo de olho e, simplesmente "desligarem", mostrando-se incapazes de autorregularem o sistema HPA (BARR, 1998).…”
Section: Cortisol Salivarunclassified